The CX leader's manual to customer excellence : brilliant basics & luminous lessons from 10 top CX leaders - Van Belleghem, Steven, ....- ([S.l] : Steven Van Belleghem, 2021)
As I look back at the past year, I can see a clear common thread running through the content I created during that period. And I believe that our dramatically changed context may have had something to do with that. Before I explain what I mean by that, allow me to expand a little bit: the COVID-19 pandemic and all the restrictions to fight it pretty much catapulted us back to basics. We were no longer allowed to travel (initially not even locally), see a movie, go to a restaurant, shop for clothes, work at the office or invite friends over. Our lives were stripped to the bare essentials: we lived and worked from home in the company of our family. And for a while, that was pretty much it. I think that, perhaps subconsciously, the power of these essentials found its way into my content. Some of my pieces were about what I call “brilliant basics”: pretty simple rules – general truths almost – for creating a fantastic CX. Other contributions were about powerful CX success stories with tricks of the trade from world leaders like Amazon, Walmart, Disney and Grab. Writing and recording all this content made me realize the power of what is essential. That is why I wanted to create this book: a compilation of my favourite basic pieces from these past few months with some brand-new unpublished ones. I wanted to share what I see as the foundation of CX and how top CX leaders envision this in order to inspire you at the level where everything is yet to take off.